Vertical distributions and diurnal variations of high‐molecular‐weight dissolved arsenic in the oligotrophic ocean. (7th April 2017) - Lee, Chih‐Ping; Cheng, Chia‐Yu; Wen, Liang‐Saw
Abstract: Arsenic (As) has long been recognized as an environmental toxicant. Its biogeochemical cycling in the ocean is often linked to that of phosphorus (P), whose dynamics may affect the efficiency of the marine carbon pump as it relates to CO2 absorption from the atmosphere. The chemical behavior of inorganic arsenate is similar to that of phosphate, and it is also taken up by phytoplankton or bacterioplankton in parallel with phosphate. This absorbed As is then metabolized into arsenite or methylated As and expelled through detoxification processes. However, in surface waters of the oligotrophic ocean where dissolved P is predominantly in organic forms, the regeneration and recycling processes of As remain unclear. Here, we demonstrate the first depth profiles of high‐molecular‐weight (HMW, 1 kDa‐0.4 μ m) As and dissolved organic phosphorus (DOP) in oligotrophic waters and their short‐term variations in the euphotic zone. HMW‐As constituted 21% ± 8% of dissolved As, whereas the high‐molecular‐weight dissolved organic phosphorus (HMW‐DOP) decreased from 74% of the total DOP at the surface to 35% at a 200 m depth. Concurrent variations of HMW‐As and HMW‐DOP in the upper euphotic zone were identified for the first time. This also provides new evidence from direct observation supporting the size‐reactivity continuum model. These temporal changes may result from light‐driven enhancement of photoheterotrophy. Overall, our results highlight the contribution of microbes to the production and assimilation of HMW materials and signify their importance in marine As and P cycles.